A micrometer head integrated microfluidic device for facile droplet size control and automatic measurement of a droplet size. Issue 5 (10th December 2019) - Bui, Hoang Khang; Seo, Tae Seok
Abstract: A novel microfluidic droplet generator is proposed, which can control the droplet size through turning an integrated micrometer head with ease, and the size of the produced micro‐droplet can be automatically and real‐time monitored by an open‐sourced software and off‐the‐shelf hardware.